2014
DOI: 10.1037/a0033818
|View full text |Cite
|
Sign up to set email alerts
|

Spatial abilities across the adult life span.

Abstract: The study investigates age-related effects across the adult life span on spatial abilities (testing subabilities based on a distinction between spatial visualization, mental rotation, and perspective taking) and spatial self-assessments. The sample consisted of 454 participants (223 women and 231 men) from 20 to 91 years of age. Results showed nonlinear age-related effects for spatial visualization and perspective taking but linear effects for mental rotation; few or no age-related effects were found for spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
55
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 49 publications
12
55
0
1
Order By: Relevance
“…Borella et al, 2014). Model 3 was similar to Model 1b, but with the addition of a direct path from WM to pointing in cardinal directions.…”
Section: Model 3: Structure and Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Borella et al, 2014). Model 3 was similar to Model 1b, but with the addition of a direct path from WM to pointing in cardinal directions.…”
Section: Model 3: Structure and Resultsmentioning
confidence: 97%
“…Wilkniss et al, 1997, or descriptions of environments -Meneghetti, Borella, Grasso, & De Beni, 2011. The few studies on the role of spatial skills in older adults' acquisition of new environments indicated that, although spatial abilities decline with aging (Borella, Meneghetti, Ronconi, & De Beni, 2014;Salthouse, Babcock, Skovronek, Mitchell, & Palmon, 1990), they are related to spatial learning. For instance, the performance of young and older adults in spatial tasks like the MRT has been found to be positively related to environment learning from a map (Meneghetti, Fiore, Borella, & De Beni, 2011;Pazzaglia & De Beni, 2006) or through real navigation (Kirasic, 2000).…”
Section: )mentioning
confidence: 98%
See 3 more Smart Citations